Morfologi Orchidaceae di Kebun Raya Liwa Kabupaten Lampung Barat Provinsi Lampung (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2018)
Research on Morphology Orchidaceae Plants in the Botanical Garden Liwa West Lampung Regency of Lampung Province, has been carried out in February - March 2017, aims to examine the types and morphological descriptions Familia Orchidaceae plants in the Botanical Garden Liwa, was conducted using descriptive survey method by doing direct observation on Nursery location in Liwa Botanical Garden. Results of the study were 25 Orchid species, namely : Agrostophyllum bicuspidatum J.J.Smith., Agrostophyllum majus Hook.F., Anoectyllus sp., Appendiculata torta Blume., Arundina graminifolia Blume., Bulbophylum lepidum J.J.Smith., Bulbophyllum phalaenopsis J.J.Smith.¸ Coelogyne asperata Lindl., Coelogyne speciosa Lindl., Dendrobium crumenatum Lindl., Dendrobium montanum J.J.Smith., Eria flavescens Blume., Eria iridifolia Hook.F., Eria nutans Lindl., Goodyera sp., Gramatophyllum speciosum Blume., Liparis gibbosa Finet., Malaxis sp., Nephelaphyllum pulcrum Blume., Paphiopedilum tonsum Rchb.F., Pholidota imbricata W.J.Hoocke., Pholidota ventricosda Blume., Pomatocalpa kunsteri Hook.F., Thecostele alata (Roxb.)Par. & Rchb.F., dan Tricotosia feroxi Blume. Species obtained has a root system fibers with root specific functions of the roots patches and aerial roots, rod-type herbaceous and pseudobulb, type of stem growth simpodial and monopodial, single leaf, leaf types of lancet, elongated, oval, swords, ribbon and heart, flowering single and plural in bunches with growth type of flos terminalis and flos axillary.ABSTRAKPenelitian tentang struktur morfologi Familia Orchidaceae di Kebun Raya Liwa (KRL) telah dilaksanakan  pada Maret-Juli 2017, bertujuan untuk mengkaji tipe morfologi akar, batang, daun dan bunga familia Orchidaceae yang tersebar di KRL, dengan mendeskripsikan  25 species Orchidaceae yaitu  Agrostophyllum bicuspidatum J.J.Smith., Agrostophyllum majus Hook.F., Anoectyllus sp., Appendiculata torta Blume., Arundina graminifolia Blume., Bulbophylum lepidum J.J.Smith., Bulbophyllum phalaenopsis J.J.Smith.¸ Coelogyne asperata Lindl., Coelogyne speciosa Lindl., Dendrobium crumenatum Lindl., Dendrobium montanum J.J.Smith., Eria flavescens Blume., Eria iridifolia Hook.F., Eria nutans Lindl., Goodyera sp., Gramatophyllum speciosum Blume., Liparis gibbosa Finet., Malaxis sp., Nephelaphyllum pulcrum Blume., Paphiopedilum tonsum Rchb.F., Pholidota imbricata W.J.Hoocke., Pholidota ventricosda Blume., Pomatocalpa kunsteri Hook.F., Thecostele alata (Roxb.) Par. & Rchb.F., dan Tricotosia feroxi Blume. Spesies yang diperoleh memiliki sistem akar serabut dengan akar khusus akar udara, batang herbaceous dan pseudobulb, jenis pertumbuhan batang simpodial dan monopodial, daun tunggal, jenis daun lanset, memanjang, oval, pedang, pita dan jantung. Bunga tunggal dan majemuk dalam tandan dengan jenis pertumbuhan flos terminalis dan flos axillar.